Printed UHF antenna for satellite communication - Rahman, Sadman Sami; Ammana, Rishfat; Arshad, Abrar; Maruf, Abdullah Al (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.